MULTIMEDIA PEMBELAJARAN BERBASIS TIK UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF KELAS IV SDN DADIREJO 01 - Aryanti, Rizka; Untari, Mei Fita Asri; Nafiah, Ulin (AGUSPATI Research Institute, 2021)
This classroom action research was carried out because the use of media in learning was less varied so that the understanding of students was less than optimal, especially the ability to think creatively. The purpose of this study was to determine the increase in creative thinking skills by using ICT-based learning multimedia. The research subjects were the fourth grade of SDN Dadirejo 01 with 16 children. The research method used is classroom action research with the Arikunto model. The research was conducted in three cycles with two actions in each cycle through the stages of planning, implementation, observation, and reflection. The indicators of creative thinking skills used are fluency, flexibility, originality, and detail. The research instruments used were observation sheets and documentation. The data analysis technique used quantitative and qualitative data. The results of the study were described through students' activities in describing information, making a list of questions, and conducting interviews. The use of ICT-based learning multimedia can increase students' creative thinking skills by 31.3%. Based on the results of data analysis, it can be concluded that the use of ICT-based multimedia can improve the creative thinking skills of fourth grade at SDN Dadirejo 01.